2019
DOI: 10.1083/jcb.201807195
|View full text |Cite
|
Sign up to set email alerts
|

Maturation-driven transport and AP-1–dependent recycling of a secretory cargo in the Golgi

Abstract: The Golgi cisternal maturation model predicts that secretory cargo proteins should be continuously present within the cisternae while resident Golgi proteins come and go. Casler et al. verify this prediction by tracking the passage of a fluorescent secretory cargo through the yeast Golgi.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
93
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 68 publications
(101 citation statements)
references
References 106 publications
7
93
1
Order By: Relevance
“…We used a pixel size of 60-70 nm, a frame size of 256 × 128 or 256 × 256 pixels, and a Z-step interval of 0.30 µm. For 4D imaging, Z-stacks were collected at intervals of 2 s. Three-color imaging using the JF 646 HaloTag dye (Grimm et al, 2015) was performed as previously described (Casler et al, 2019). The image stacks were deconvolved using Huygens Professional software and further processed using ImageJ (National Institutes of Health; Schneider et al, 2012).…”
Section: Construction Of a Strain Expressing Tagged Sec63mentioning
confidence: 99%
“…We used a pixel size of 60-70 nm, a frame size of 256 × 128 or 256 × 256 pixels, and a Z-step interval of 0.30 µm. For 4D imaging, Z-stacks were collected at intervals of 2 s. Three-color imaging using the JF 646 HaloTag dye (Grimm et al, 2015) was performed as previously described (Casler et al, 2019). The image stacks were deconvolved using Huygens Professional software and further processed using ImageJ (National Institutes of Health; Schneider et al, 2012).…”
Section: Construction Of a Strain Expressing Tagged Sec63mentioning
confidence: 99%
“…To counter these problems, we used an alternative system that allowed synchronized release of bound fluorescent cargo from the ER (Casler, Papanikou et al 2019). In this system, the cargo, a modified DsRed-Express2, forms homo-aggregates in the ER lumen when expressed.…”
Section: Do Secreted Proteins Traffic Through Dispersed Golgi Membranmentioning
confidence: 99%
“…Other cDNAs generously provided include: St3-eGFP from Dr. Sakari Kellokumpu, (University of Oulu, Oulu, Finland), GalNAc T2-mCherry from Dr. Dibbyendu Bhattacharya (Tata Memorial Center, Mumbai, India), GalT-3xGFP and mCherry-Sec23 from Dr. Jennifer Lippincott-Schwartz (HHMI, Janelia Research Campus), GM130 GFP from Dr. Christine Suetterlin (University of California, Irvine, CA), pDsRed-ER (Takara Bio, CA), RUSH-GPI-mApple, Rush-GPI-Halo, and Ensconsin-mCherry (Addgene, MA). For imaging ER bulk flow trafficking to Golgi, a bicistronic plasmid encoding a modified DsRed-Express2 cargo (Casler, Papanikou et al 2019) and ManII-GFP was generated in the laboratory of Benjamin Glick (University of Chicago, Chicago, IL). The M. musculus ManIIA1gene was obtained from BioBasic (Toronto, Canada), PCR amplified and inserted into the DsRed-Express2 plasmid using in-fusion cloning (Takara Bio, CA).…”
Section: Antibodies Cdna Constructs and Reagentsmentioning
confidence: 99%
“…The recycling of glyco-enzymes requires specific adaptors that gate their entry into COPI coated retrograde transport vesicles. Among the adaptors so far identified the COPI  and  subunits and the Golgi phosphoprotein 3 (GOLPH3) are the best characterized (Casler et al, 2019;Liu et al, 2018;Schmitz et al, 2008;Tu et al, 2008). The role of GOLPH3 in enzyme recycling was first demonstrated in yeast by Banfield and Burd (Schmitz et al, 2008;Tu et al, 2008) and later shown to be conserved in metazoa including mammals (Ali et al, 2012;Chang et al, 2013;Eckert et al, 2014;Isaji et al, 2014;Pereira et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…This results in the incorporation of the Vps74p clients into COPI recycling vesicles and hence in their retrograde transport within the secretory pathway. Thus, changing the levels of Vps74p alters the distribution of the Vps74p clients across the transport stations (Casler et al, 2019;Liu et al, 2018;Schmitz et al, 2008;Tu et al, 2008;Wood et al, 2009). Importantly, the human GOLPH3 gene is amplified in solid tumors where it stimulates mitogenic signaling and cell proliferation, acting as an oncogene (Scott et al, 2009).…”
Section: Introductionmentioning
confidence: 99%